2014
DOI: 10.1371/journal.pone.0104148
|View full text |Cite
|
Sign up to set email alerts
|

The Scavenger Receptor MARCO Modulates TLR-Induced Responses in Dendritic Cells

Abstract: The scavenger receptor MARCO mediates macrophage recognition and clearance of pathogens and their polyanionic ligands. However, recent studies demonstrate MARCO expression and function in dendritic cells, suggesting MARCO might serve to bridge innate and adaptive immunity. To gain additional insight into the role of MARCO in dendritic cell activation and function, we profiled transcriptomes of mouse splenic dendritic cells obtained from MARCO deficient mice and their wild type counterparts under resting and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…52 However, MARCO does not exclusively exist on M2 macrophages being associated with M1 and dendritic cell activation. [53][54][55] Increased CXCL12 promotes neo-angiogenesis, and supported by increased expression of SRPX2, may also mediate angiogenesis providing further evidence that tumorassociated macrophages in telomerase with macrophages are more tumor-promoting compared with those in alternative lengthening of telomeres with macrophages. 56,57 Telomerase with macrophage tumors were associated with a reduced extent of surgical resection, suggesting tumor-associated macrophages in telomerase with macrophages are more infiltrative and thus damaging.…”
Section: Discussionmentioning
confidence: 88%
“…52 However, MARCO does not exclusively exist on M2 macrophages being associated with M1 and dendritic cell activation. [53][54][55] Increased CXCL12 promotes neo-angiogenesis, and supported by increased expression of SRPX2, may also mediate angiogenesis providing further evidence that tumorassociated macrophages in telomerase with macrophages are more tumor-promoting compared with those in alternative lengthening of telomeres with macrophages. 56,57 Telomerase with macrophage tumors were associated with a reduced extent of surgical resection, suggesting tumor-associated macrophages in telomerase with macrophages are more infiltrative and thus damaging.…”
Section: Discussionmentioning
confidence: 88%
“…Many SR ligands are also recognized by and trigger cell signaling through TLRs. It has been demonstrated that SRs internalize such ligands to render them accessible to TLR3, TLR7/8 and TLR9 localized in the cytosol [146,147]. Taking into account such findings, SRs were also proposed as a potential target for anticancer vaccine delivery to DCs.…”
Section: Scavenger Receptor Targetingmentioning
confidence: 99%
“…MARCO is expressed on restricted subsets of macrophages, and its expression can be induced at sites of inflammation after bacterial infection . Moreover, MARCO seems to play a role in inflammatory responses other than the typical functions of macrophage recognition and clearance of pathogens and their polyanionic ligands . Mice deficient in MARCO exhibit significantly impaired clearance of Streptococcus pneumonia from the nasopharynx and abrogated cytokine production and cellular recruitment to the nasopharynx following colonization .…”
Section: Introductionmentioning
confidence: 99%
“…3 Moreover, MARCO seems to play a role in inflammatory responses other than the typical functions of macrophage recognition and clearance of pathogens and their polyanionic ligands. 4 Mice deficient in MARCO exhibit significantly impaired clearance of Streptococcus pneumonia from the nasopharynx and abrogated cytokine production and cellular recruitment to the nasopharynx following colonization. 5 MARCO and SR-AI/II are required for silica-induced mast cell activation, leading to the production of tumor necrosis factor-α and reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%